Les interactions verbales dans les émissions télévisuelles algériennes - OUTALEB- PELLÉ, Aldjia; AZIL, Amina Amel (Journal of Human Sciences, 2016)
Our researchwork examines the specific features of mediated verbal interactions in Algerian televisions. Itsprimary aim is to study  code switching and discoursecooperation in four TV programs : ‘ Paroles de Femmes’, ‘A CœurOuvert ‘, ‘ Bonjour d’Algérie  ‘ in Canal Algerie TV  and ‘ Controverse ‘ in Dzair TV. Afterrecording and transcribing phonetically eightseries of the cited TV programs, weadopted the interdisciplinary inductive approachto analyse our corpus. Thus, the results of ouranalysis revealed that participants alternateFrench, Algerian Arabicdialect, English and Tamazight in theirmediated interactions in order to co-construct their verbal discourse, intended to bebroadcasted to the general public.